Principles of Management for the Hospitality Industry - Tesone Dana (Elsevier - Butterworth Heinemann, 2010)
This book is an up-to-date and skillful integration of all core areas of Management. Preface, Management Knowledge, Managing Service Enterprises, Management Practice and Evolution and Ethics, Strategic Planning and Problem Solving and Decisions, Systems and Development and Structures, Management Functions, Productivity and Value-Added Management Practices, Organizing Resources and Structure and Systems, Human Resource Management and Influence Skills, Managing Technology and Marketing Systems, Management Control Functions, Strategic Applications, Tactical Productivity Strategies, Tactical Growth Strategies, Tactical Turnaround Strategies, Leadership Applications, Leadership Awareness, Leadership Practice, Organizational Behavior and Leadership Development, Sustainability, Sustainable Hospitality Marketing Management, Development of a Sustainable Tourism Hospitality Human Resources Management Module, Glossary of Terms, Index.